Reaction pathway of poly(ethylene) terephthalate carbonization: Decomposition behavior based on carbonized product. (1st May 2020) - Chia, Jennifer W.F.; Sawai, Osamu; Nunoura, Teppei
Graphical abstract: Highlights: Operating condition at 400–480 °C produces char with the highest fixed-carbon content. Rapid decomposition of PET occurs through decarbonylation to form char. PET decomposed to form wax with high atomic H/C and O/C ratio. Release of CO and CO2 due to scission of CO bond leads to the formation of char. The degree of cross-linking is a suitable indicator for the formation of char. Abstract: Char, a solid product obtained from carbonization of waste Poly(Ethylene) Terephthalate (PET), has high potential to solve the current plastic waste problem through the synthesis of new carbon-based adsorbents. However, thermal degradation reaction of polymer involves multiple series of complex reaction pathways and the formation of char is not clarified. In this study, the phase behavior of PET carbonization and the mechanism of char formation was studied in detail. Based on the van Krevelen diagram, it is evident that rapid thermal decomposition of PET occurs through decarbonylation to form char and decarboxylation to form wax. Based on the analysis of cross-linking behavior, a correlation between the degree of cross-linking as a function of CO and CO2 and dependent parameters based on the experimental operation was obtained. The findings validified the assumption that scission of CO bond in the ester group through decarbonylation and decarboxylation to release CO and CO2 leads to the formation of char. The cross-linking behavior was further clarified by studying the distribution of cross-linking structure in char and wax. It was confirmed that decarbonylation reaction to release CO is highly associated with the formation of cross-linking to form char in the solid residue, whereas decarboxylation reaction to release CO2 is highly associated with the formation of cross-linking to form aromatic compounds in the wax residue.